A study on the difficulties encountered by foreign students in using the UP Diliman Libraries - Perez, Freya Faye L.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This research ascertained what difficulties foreign students encounter while they are using the libraries in UP Diliman. The difficulties that are determined in the study are in relation with the UP Diliman libraries' collection, facilities, user services and staff. The foreign students enrolled in UP Diliman for the second semester of Academic Year 2004-2005 are the respondents of the research.
The study used questionnaire as research instrument which were distributed to the respondents. Of the total foreign student population, 93 questionnaires were retrieved and were given back to the researcher. The data collected from the questionnaires were tabulated, collated and were analyzed using frequency distribution. On the other hand, interview with the head librarians and staff of the colleges with foreign students as well as the Main Library was conducted to gather information regarding their library orientation program and library guides that they provide for the use of foreign students.
Findings of the study showed that a number of difficulties are encountered or experienced by foreign students while they are using the UP Diliman libraries. In terms of the libraries' collection, it is with the arrangement of library materials and resources that foreign students encounter difficulties specifically with the location of these materials. With regard to the library staff/personnel, the result of the study showed that majority of the foreign students does not experience much difficulty when dealing with them and even find them efficient and accommodating to their needs. On the other hand, computer terminals are the library facilities that foreign students find difficult to use.
With the library user services available in UP Diliman libraries, book lending is still the most utilized and generally, foreign students have a positive view regarding the other library user services in the libraries. With regard to the library orientation program conducted by the college libraries and the Main Library, the researcher found out that no special library orientation is intended specifically for foreign students. These foreign students along with the other new students of the colleges are oriented all at the same time. Library guides and handouts are also the same for all students which mean that the college libraries do not provide special handouts or guides for foreign students.
After having identified the difficulties encountered by foreign students, the researcher posted some recommendation at the end of the study that can be employed so that these special users of the UP Diliman libraries (foreign students) will be more satisfied and confident in using the libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Libraries; Students, Foreign -- Books and reading -- Philippines -- Quezon City; Libraries -- Library use studies